Solving a century-old conundrum: genetic integrity of a rare and local endemic shrub facing introgression with a widespread congener - Atikessé, Alice; Sirois, Luc; de Lafontaine, Guillaume (Botanical journal of the Linnean Society, 2025)
Hybridization is a key driver of evolutionary processes and speciation. Advances in sequencing technology provide unprecedented opportunity to study discriminating phenotypic characters at the molecular level and identify candidate loci associated with the speciation process. Salix chlorolepis is a rare and threatened endemic shrub species restricted to the upper slopes of Mount Albert (Canada) proposed to hybridize with S. brachycarpa, a locally abundant geographically widespread congener. We aimed to characterize rangewide genetic variation of S. chlorolepis, establish whether it actually hybridizes with S. brachycarpa, and assess whether leaf pilosity is an indicative variable phenotypic trait related to introgressive hybridization. Using single nucleotide polymorphism data, we inferred patterns of genetic structure and diversity. We tested for genetic associations with environmental distance, taxonomic identity, or phenotypic variability in leaf hair density using populations genomics approaches at the multilocus (partial Mantel tests and generalized dissimilarity models) and single-locus (latent factor mixed model, pRDA, PCAdapt, OutFLANK) levels. Although a common genetic ancestry persists within S. chlorolepis, fine-scale spatial genetic structure reflects its fragmented distribution. Interspecific genetic admixture in sympatry zones corroborates the existence of introgressive hybridization. Leaf pilosity is an important variable explaining multilocus genotype variation between the two taxa. We flagged nine candidate loci that are both strongly associated with leaf pilosity phenotype and with divergent selection between taxa. The existence of such loci ‘impermeable’ to introgression ensures maintenance of interspecific barrier and clear phenotypic differentiation between species. Such genomic heterogeneity alleviates assimilation risk of the rare and threatened species by its more abundant congener despite ongoing introgression.